Konzeption von Verfahren zur kamerabasierten Analyse und Optimierung von Drehrohrofenprozessen - Waibel, Patrick (Schriftenreihe des Instituts für Angewandte Informatik - Automatisierungstechnik, Karlsruher Institut für Technologie, 2014)
The aim of this work was the development of new image processing methods for the analysis and optimization of rotary kiln processes. It is shown how the newly developed methods can be employed to analyze certain areas and effects of rotary kiln processes. Thereby gained new process information can be used in the process control to optimize rotary kiln processes in terms of economic and environmental objectives.